A 10-year experience of hydatid cysts of lung in association with other extrathoracic system involvement in a tertiary care hospital in Kolkata, India - Surendra Singh Yadav; Ushnish Chakrabarty; Swarnendu Datta; Madhusudan Pal (Asian Journal of Medical Sciences, 2022)
Background: The metacystode of tapeworm Echinococcus causes hydatid disease. Infection in man is mainly caused by Echinococcus granulosus. Surgical intervention to treat complicated hydatid cyst (HC) is different from uncomplicated HC. Aims and Objectives: The present study was performed with an aim to review 82 cases of pulmonary HCs and associated HCs in other locations. We analyze and evaluate our experience in the surgical treatment and complication. Materials and Methods: In a 10-year period, from August 1, 2005, to July 31, 2015; 82 patients were operated on in our hospital for HCs in pulmonary as well as other associated extrapulmonary locations. The diagnosis was established on the basis of clinical features and imaging studies supplemented by serological test. Surgical approach consisted of a posterolateral thoracotomy in all cases of thoracic HCs. For cysts in extrathoracic locations, either laparotomy or local excisions were performed. Results: Radical resections [lobectomy] were done in four cases, and conservative operations in the remaining. Post-operative complications occurred in 12 cases (14.63 %). We had two recurrences, three cases of prolonged air leak with bronchopleural fistula, two had atelectasis, and five wound infections. At 6 months follow-up, 97.56% of our patients were free of any recurrence. Conclusion: HCs of the lung are best treated with surgery. Even when associated with HCs in other locations in the body, surgery is considered the treatment of choice. When supplemented with long-term perioperative Albendazole therapy, the chance of recurrence is practically negligible.